DAMPAK KETERLIBATAN PELANGGAN, DAN PENGGUNAAN MEDIA SOSIAL TERHADAP PERTUMBUHAN USAHA MIKRO, KECIL, DAN MENENGAH DI BY.NEIRA - Nakiza, Eka Septianus (Jurnal Pijar, 2024)
Social media as a marketing tool can be utilized to engage customers and build brand affinity. Customer engagement is a psychological process that creates an emotional bond between the customer and the brand, ultimately increasing customer loyalty and satisfaction. By Neira applies this concept by actively inviting customers to share their experiences through reviews and photos on social media. This research method uses a qualitative approach with descriptive research motede. Currently, ByNeira has 2,415 followers and 88 posts on its Instagram account. So far, all social media owned by ByNeira is still managed directly by the owner, in the sense that there is no special staff in charge of managing social media. As for the technology carried out by ByNeira, one of them is the existence of a non-cash payment system through Qris where consumers can pay by simply scanning the barcode at the cashier's desk, the choices are quite diverse, can use GoPay, Ovo and Mbanking. Since using social media, ByNeira has managed to increase sales turnover by around 20-30% compared to before